Web-Based Waste Recording Application At The Mandiri Waste Bank Of Kayu Putih Village - Nur Rachma; Dewi Estri Jayanti; Alkat Zakaria; Dannie Ferbrianto; Rachmat Setiabudi (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2024)
The waste bank program launched by the government is a means of education and forming good waste management behavior in the community. The Mandiri waste bank in Kayu Putih subdistrict, East Jakarta, still records its waste management manually and often faces various obstacles, such as recording errors, missing historical data, and a lack of transparency. The aim of this research is to overcome the problems that occur at the Mandiri waste bank, Kayu Putih Village, East Jakarta and implement a web-based application which is expected to increase effectiveness and efficiency in the recording and administration process carried out by the waste bank management. This application is designed to make it easier to record customer data, numbers and the type of waste deposited and calculating the economic value of the waste. The system development method used includes user needs analysis, system design using UML (Unified Modelling Language), coding with framework web-based, and implementation/testing. This research succeeded in increasing the operational efficiency of waste banks, reducing recording errors, and encouraging active community participation in waste sorting and recycling activities. With the results achieved, it is hoped that this web-based waste recording application can become a sustainable waste management solution in the Kayu Putih Subdistrict area, East Jakarta.